STRIGA HERMONTHICA SEED GERMINATION THROUGH ROOT EXUDATES OF INDIGENOUS SUB-SAHARAN WEED SPECIES - Nijkamp, Randy Trinity; Nakorn, Somporn na (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
This study was conducted to evaluate root exudates from sub-Saharan indigenous weed species to induce germination of Strigahermonthica(Del.) Beth., a root parasitic weed.Significant variation in Striga seed germination was observed, ranging from an absence to the induction of 74.1% Striga seeds. Direct comparison of Striga germination was obscured by differences in weed root biomass as within most of the species, a direct proportional relation between Striga seed germination and weed root dry weight was observed. Expression of Striga seed germination in % g-1root dry weight (GIC) was found a suitable solution, as stable values for GIC were obtained, despite considerable variation in root dry weight. GIC was significant for 25 species and highest with Commelinaforskalaeiand Sesamumalatum(9.91; 9.78 % g-1 dry root, respectively). Striga seeds did not germinate following application of exudates from Mitracarpusscaberand Phyllanthuspentrandus. These results show that a substantial number of indigenous weed species may serve as alternative trap crops to control the parasites seed bank. Furthermore, the timing of weeds in the cropping system may provide a (partial) explanation for the erratic infestation levels found across fields and years that has dazedresearchers for many years. Keywords: Strigahermonthica, seed germination, indigenous weeds, root exudates, seed bank